2007
DOI: 10.1295/polymj.pj2007053
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of Grafted Copolymer on Colloidal Silica and Introduction of Surface Amino Group

Abstract: ABSTRACT:To obtain polymer-modified silica (550 nm diameter), trimethoxysilyl-terminated poly(glycidyl methacrylate-co-methyl methacrylate) with epoxy ring (to prevent the formation of carboxyl group) was successfully synthesized. Then, the cross-linking of the grafted copolymer on silica was made using ethylenediamine or hexamethylenediamine of varying alkyl chain lengths, and the stability of cross-linked silica particles was investigated in alkaline aqueous solution. Cross-linked polymer-modified silica bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The presence of epoxy groups allows a number of chemical modifications on the initial polymer to suit a variety of applications. Consequently, preparation of GMA-based copolymers and their modifications is the subject of numerous papers [10][11][12][13][14][15][16][17][18][19][20][21][22]. The conducted studies had indicated that an amine group is one of the most efficient functional groups for heavy metal ion removal.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of epoxy groups allows a number of chemical modifications on the initial polymer to suit a variety of applications. Consequently, preparation of GMA-based copolymers and their modifications is the subject of numerous papers [10][11][12][13][14][15][16][17][18][19][20][21][22]. The conducted studies had indicated that an amine group is one of the most efficient functional groups for heavy metal ion removal.…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C MAS NMR spectrum of homopolymer poly-GMA, presented in Figure a, shows resonance peaks at 16 ppm for 3 ( C H 3 −), 55 ppm for 1 (H 2 C CCH 3 COCH 2 ), 45 ppm for 2 (H 2 C C CH 3 COCH 2 ), 67 ppm for 5 (−O– C H 2 −), and 177 ppm for 4 (−O­( C O)­C−) . The resonance peaks of 6 at 49 ppm and 7 at 44 ppm were assignable to CH and CH 2 of the epoxy ring.…”
Section: Resultsmentioning
confidence: 99%
“…13 C MAS NMR spectra of homopolymers, poly­(glycidyl methacrylate) (poly-GMA), poly­(ethylene glycol dimethacrylate) (poly-EGDMA), and initial copolymers poly­(GMA- co -EGDMA) with 60 and 80 mass % of GMA are presented in Figures a,b,c and S1 (Supporting Information), respectively. The assignments of the NMR resonance signals have been made by comparison with spectra of analogous chemical groups taken from the previously reported investigation. …”
Section: Resultsmentioning
confidence: 99%